We Were on a Trip (2008)
EAFIT Children's University participated in the II Conference on Science, Technology and Innovation, held at the University of Concepción, Chile. Team members attended lectures such as "Narrativity and practical knowledge in collective action: the application of the model to communication about Science, Technology and Innovation"; workshops such as "We make science fun" with Modesto Tames from the Exploratorium Museum in San Francisco, United States. EAFIT Children's University also had a space to present itself.